An Analysis of Students’ Questioning Skill in English Foreign Language Class - Mohammad Firmansyah; Mohammad Mohammad Rafi'i Sata (Universitas Bengkulu, 2021)
This Research aimed to know the level of questions used by students and to know the student’s factors to ask questions in classroom at sixth semesters at Madako University. This research employed descriptive qualitative research. The samples of the research were five students at class A which were selected purposively. The techniques for collecting data used observation checklist, interview, and documentation. The obtained data were percentage and analyzed based on interactive model of Miles & Huberman, some steps among data reduction, data display, and conclusion drawing. The result of the observation showed that C1 (remembering) (13.3%), C2 (understanding) (26.6%), (analyzing) (33.4%), and (evaluating) (26.7%), while analyzing was a level the most frequently used by the students. The result of interview there were two factors namely: internal and external in internal factor the researcher found that Interest and motives of student curiosity. In external factor that the researcher found lecturer’s factor (motivation of the lecturer) and environmental’s factor. Therefore, the researcher conclude that the student at sixth semester at Madako University have the skill of questions in level medium because most of them only used questions analysis, and they have two factors to ask question, they are internal and external factors.